2005
DOI: 10.1073/pnas.0506351102
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of breast cells by truncated neurokinin-1 receptor is secondary to activation by preprotachykinin-A peptides

Abstract: breast cancer ͉ cytokines ͉ bone marrow metastasis ͉ substance P ͉ tachykinin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(116 citation statements)
references
References 28 publications
7
109
0
Order By: Relevance
“…For instance, until recently, little attention has been given to the different splice variants of NK1R. Previous studies pointed out the central role of NK1R-tr in breast cancer (104,105). Likewise, Gillespie et al analyzed NK1R-tr and NK1R-fl in colitis-associated cancer and found that it was the expression of NK1R-tr alone that predicted the progression from quiescent colitis to highgrade dysplasia and cancer (106).…”
Section: Therapeutic Innovations In Hepatoblastoma the Nk1r As A Tumomentioning
confidence: 99%
“…For instance, until recently, little attention has been given to the different splice variants of NK1R. Previous studies pointed out the central role of NK1R-tr in breast cancer (104,105). Likewise, Gillespie et al analyzed NK1R-tr and NK1R-fl in colitis-associated cancer and found that it was the expression of NK1R-tr alone that predicted the progression from quiescent colitis to highgrade dysplasia and cancer (106).…”
Section: Therapeutic Innovations In Hepatoblastoma the Nk1r As A Tumomentioning
confidence: 99%
“…Cytokine protein analyses were performed as described (22). Briefly, RayBio Cytokine Ab Arrays 3 and 5 membranes were incubated for 1 h in media, followed by consecutive incubations with biotin-conjugated cytokine Abs and HRP-streptavidin.…”
Section: Cytokine Microarraysmentioning
confidence: 99%
“…Compared with full-length (fl-TACR1), tr-NK1R lacks 96 amino acids at the cytoplasmic C-terminus of the receptor that are responsible for intracellular signal transduction. Although this splice variant is considered to be able to couple G proteins, it exhibits decreased efficiency with respect to internalization and desensitization (8,(13)(14)(15). The net result of this is a decreased ability for negative feedback inhibition, allowing constant activation despite saturation of the receptor complex (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%